Short-Term Effects of Elexacaftor/Tezacaftor/Ivacaftor Combination on Glucose Tolerance in Young People With Cystic Fibrosis—An Observational Pilot Study - Korten, Insa; Kieninger, Elisabeth; Krueger, Linn; Bullo, Marina; Flück, Christa E.; Latzin, Philipp; Casaulta, Carmen; Boettcher, Claudia (Frontiers in Pediatrics, 2022)
Background: The effect of elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) on glucose tolerance and/or cystic-fibrosis-related diabetes (CFRD) is not well understood. We performed an observational study on the short-term effects of ELX/TEZ/IVA on glucose tolerance. Methods: 16 adolescents with CF performed oral glucose tolerance tests (OGTT) before and four to six weeks after initiating ELX/TEZ/IVA therapy. A continuous glucose monitoring (CGM) system was used three days before until seven days after starting ELX/TEZ/IVA treatment. Results: OGTT categories improved after initiating ELX/TEZ/IVA therapy (p = 0.02). Glucose levels of OGTT improved at 60, 90 and 120 min (p < 0.05), whereas fasting glucose and CGM measures did not change. Conclusions: Shortly after initiating ELX/TEZ/IVA therapy, glucose tolerance measured by OGTT improved in people with CF. This pilot study indicates that ELX/TEZ/IVA treatment has beneficial effects on the endocrine pancreatic function and might prevent or at least postpone future CFRD.